1972
DOI: 10.1071/bi9720921
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of 14Co2 by Flowering and Non-Flowering Glumes of the Wheat Ear, and the Pattern of Transport of Label to Individual Grains

Abstract: This paper explores the possible role of photosynthesis by individual glumes in influencing the growth rates of individual grains of the wheat ear. Specifically we determined: (1) the photosynthetic capacities of individual glumes (i.e. nonflowering glumes, lemmas, and paleas) of an awned wheat cultivar; (2) the pattern of translocation of 14C-Iabelled assimilate from individual glumes to individual grains; and (3) the time course of translocation of label from glumes and flag leaf to the grain.The lemmas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 5 publications
(12 reference statements)
2
8
0
Order By: Relevance
“…Assimilate is generated mainly from the spike, the flag leaf and its sheath. Nonetheless, it has been long recognized that awns can substantially increase spike photosynthesis and yields under dry conditions (Atkins and Norris, 1955;Bremner and Rawson, 1972;Evans et al, 1972;Olugbemi et al, 1976). Our observations are consistent with this notion, since awnedness is much more prevalent in regions where severe drought stress is common (Fig.…”
Section: Awnednesssupporting
confidence: 89%
“…Assimilate is generated mainly from the spike, the flag leaf and its sheath. Nonetheless, it has been long recognized that awns can substantially increase spike photosynthesis and yields under dry conditions (Atkins and Norris, 1955;Bremner and Rawson, 1972;Evans et al, 1972;Olugbemi et al, 1976). Our observations are consistent with this notion, since awnedness is much more prevalent in regions where severe drought stress is common (Fig.…”
Section: Awnednesssupporting
confidence: 89%
“…If we consider the curve for grain a in the absence of others (Fig. 2a), we see that it departs from the pattern of control ears in approximately the same spikelets as does the curve for c, and that there is a suggestion of a similar relation between the curves for b and d. The members of each pair occur on the same side of the rachilla, and there is some affinity between such pairs in their vascular connections (Bremner and Rawson 1972).…”
Section: Growth Potential Of Individual Grainsmentioning
confidence: 83%
“…In all three treatments, ear photosynthesis was prevented by immersion of the ears in a 3 x M solution of DCMU [3-(3,4-dichloropheny1)-1,l-dimethylurea for 30 s; this was repeated whenever routine gas-analysis checks indicated any recovery of ear photosynthesis. The rationale for the DCMU treatment was that, as the distribution of assimilate originating in the ear favours distal grains (Bremner and Rawson 1972), ear photosynthesis might obscure the pattern of distribution of material from the remainder of the shoot which, as the main source of assimilate for grain filling, was our primary interest.…”
Section: Increase In Competition Between Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been long recognized that awns can substantially increase spike photosynthesis and subsequently yields under dry conditions (Bremner and Rawson 1972;Olugbemi et al 1976;Atkins and Norris 1955). Our data showed that the awned varieties including graecum Körn., erythrospermum Körn., ferrugineum (Alef.)…”
Section: Discussionmentioning
confidence: 44%